Ashes Victory : The Official Story of the Greatest Ever Test Series in the Team's Own Words - England Cricket Team (London Orion, 2005)
Written from the viewpoint of the changing room and the middle of the pitch, this is an account of England's progress in the Ashes series. Here, the players reveal their emotions at key moments, and explain how they set about taking on the formidable Aussies. It contains photographs of the best action and behind-the-scenes moments.
Include Epilogue and Illustration
Keywords: Test matches (Cricket) -- Australia -- England